Profile Physical Condition Of Tangerang City Athletes In Preparation For Porprov Banten In 2022 - Iwan Hermawan; Fahmy Fachrezzy; Puspo Nagati Paramita Namira Khanza; Haris Nugroho; Nurhidayat Nurhidayat (Universitas Bengkulu, 2021)
The purpose of this study was to determine the profile of the physical condition of athletes in the city of Tangerang in preparation for the sports week of Banten province in 2022. The research method used quantitative descriptive, the population and sample in this study were 40 athletes of Porprov Banten, and the sampling technique used purposive sampling by taking into account the characteristics gender, namely 20 sons and 20 daughters, while the data collection technique was through tests and anthropometric measurements and components of physical condition. Data analysis uses descriptive frequency analysis using the formula where P is the percentage sought, F = Frequency and N = Number of samples, overall descriptive analysis of frequency using Microsoft Excel 2019. The results of this study can be concluded that (i) anthropometry consisting of height and weight; and (ii) the physical condition component consists of leg muscle explosive power, abdominal muscle strength, endurance, agility, and speed. This study only involves physical and anthropometric components, for further research by considering social, family, psychological and related environmental factors in improving the achievements of Banten Province athletes